AKTIVITAS DOMESTIK DAN PUBLIK PEREMPUAN KERJA (STUDI TERHADAP PEREMPUAN PEDAGANG KELONTONG DI PEKAPURAN RAYA BANJARMASIN) - Sigit Ruswinarsih (Kafa`ah: Journal of Gender Studies, 2013)
This article describes the role of women in domestic and public sphere. Multi-role women are able to maintain harmonious relations in their extended and core families. The main reason women have trading activities because of economic pressures. They feel they have a responsibility for their family livelihood sustainability. The interesting thing is  they aware that their contributions to supplement their family income does not necessarily revoke roles as wife and mother in their family.Thus the women's role to implement various strategies in order to run smoothly, both in domestic and public aspects. Keywords : Women have  trading, domestic and public activityCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.71